EMOTIONAL MATURITY OF HIGHER SECONDARY SCHOOL STUDENTS OF ERNAKULAM DISTRICT, KERALA - TES THOMAS *; LIZMITHA GODWIN (The Journal of Research ANGRAU, 2022)
The study aimed to analyze the emotional maturity of higher secondary school students in Kerala. Using a simple random sampling, 100 adolescents between the age of 16 and 17 years from five higher secondary schools situated in the Ernakulam district of Kerala were selected for the study. The data was collected from December 2021 to March 2022. The standardized emotional maturity scale developed by Dr. Yashvir Singh and Dr. Mahesh Bhargava (1990) was used to collect the data. The results indicated that nearly fifty per cent of the students (41%) were in the condition of ‘extremely unstable’. The difference between girls and boys in the level of emotional maturity was not significant, but girls showed higher emotional maturity than boys. Adolescents from rural areas showed higher emotional maturity than adolescents from urban areas, and the difference was significant concerning, emotional regression, social maladjustment, personality disintegration and lack of independence. Further, it is found that emotional instability, regression, social maladjustment, personality disintegration and lack of independence are positively correlated with each other.